Alimentary fluoride intake in preschool children - Oganessian, Edgar (BioMed Central, 2011)
BACKGROUND: The knowledge of background alimentary fluoride intake in preschool children is of utmost importance for introducing optimal and safe caries preventive measures for both individuals and communities. The aim of this study was to assess the daily fluoride intake analyzing duplicate samples of food and beverages. An attempt was made to calculate the daily intake of fluoride from food and swallowed toothpaste. METHODS: Daily alimentary fluoride intake was measured in a group of 36 children with an average age of 4.75 years and an average weight of 20.69 kg at baseline, by means of a double plate method. This was repeated after six months. Parents recorded their child's diet over 24 hours and collected duplicated portions of food and beverages received by children during this period. Pooled samples of food and beverages were weighed and solid food samples were homogenized. Fluoride was quantitatively extracted from solid food samples by a microdiffusion method using hexadecyldisiloxane and perchloric acid. The content of fluoride extracted from solid food samples, as well as fluoride in beverages, was measured potentiometrically by means of a fluoride ion selective electrode. RESULTS: Average daily fluoride intake at baseline was 0.389 (SD 0.054) mg per day. Six months later it was 0.378 (SD 0.084) mg per day which represents 0.020 (SD 0.010) and 0.018 (SD 0.008) mg of fluoride respectively calculated per kg bw/day. When adding the values of unwanted fluoride intake from the toothpaste shown in the literature (0.17-1.21 mg per day) the estimate of the total daily intake of fluoride amounted to 0.554-1.594 mg/day and recalculated to the child's body weight to 0.027-0.077 mg/kg bw/day. CONCLUSIONS: In the children studied, observed daily fluoride intake reached the threshold for safe fluoride intake. When adding the potential fluoride intake from swallowed toothpaste, alimentary intake reached the optimum range for daily fluoride intake. These results showed that in preschool children, when trying to maximize the benefit of fluoride in caries prevention and to minimize its risk, caution should be exercised when giving advice on the fluoride containing components of child's diet or prescribing fluoride supplements.